TOTAL PHENOLIC, FLAVONOID CONTENT, AND ANTIOXIDANT ACTIVITY OF JUSTICIA TRANQUEBARIENSIS L.F. AND CYCAS BEDDOMEI DYER. LEAVES (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Polyphenolics such as tannins and flavonoids are proved as powerful antioxidants to resolve cellular stress, sustain homeostasis in the body and prevent stress-associated disorders. Plant-based medicine gained importance due to its safety margin and multiple benefits. Regular intake of antioxidants is an alternative to avoid serious illness. The current investigation is aimed to measure the phenolic, flavonoid content, the antioxidant activity of Justicia tranquebariensis L.f. and Cycas beddomei leaves. The selected plants are used by tribes and traditional medicine to cure various diseases. Total phenolic content was estimated using the Folin–Ciocalteu colorimetric method, taking gallic acid as standard. At the same time, total flavonoid content was determined by aluminum chloride colorimetric assay using Rutin as standard. The absorbance was measured at 760 nm and 510 nm, respectively. Antioxidant activity was measured by two In vitro methods (DPPH and NO free radical scavenging assay) using standard protocols, where Ascorbic acid served as a reference standard. Results disclosed that the total phenolic content for the methanolic extracts of C. beddomei (36.14 ± 1.72) and J. tranquebariensis (28.57 ± 0.91) was found to be higher than petroleum ether extracts. Similarly, C. beddomei (28.13 ± 2.48) is richer in flavonoids than J tranquebariensis (20.32 ± 1.24). In DPPH assay, methanolic extract C. beddomei (78.21%) is more effective to inhibit the free radicals than J. tranquebariensis (73.05%) with IC50 values 41.55μg/ml & 59.52 μg/ml respectively at higher doses that are comparable to standard ascorbic acid (84.34%, IC50 =63.27 μg/ml). Similarly, in NO free radical scavenging assay, methanolic extract of C. beddomei (72.54%) stood best among all to scavenge the free radicals with IC50 values 50.06 μg/ml, whereas ascorbic acid is found to inhibit 83.26% with IC50 values 39.75μg/ml. The presence of various secondary metabolites such as alkaloids, carbohydrates, phenols, steroids, terpenoids, glycosides, saponins, especially tannins and flavonoids, either alone or in combination, may be responsible for the observed scavenging property. The quantity of the phenolic compounds and flavonoids can be directly correlated to the exhibited activity.